SUPLEMENTASI FISH NUGET (tuna yellowfin) SEBAGAI ALTERNATIF SCHOOL LUNCH FEEDING, KECUKUPAN PROTEIN, PENINGKATAN STATUS GIZI DAN FUNGSI KOGNITIF PADA SISWA GIZI KURANG DI SDN MALALAYANG - Olga Lieke Paruntu; I Made Djendra (Jurnal GIZIDO, 2012)
Protein Energy Malnutrition (PEM) is the state of someone who is malnourished due to thelow energy consumption of protein in the daily diet and or disruption of certain diseases.Child called Protein Energy Malnutrition was when weight is less than 80% of the indexweight for age (W / A) standard WHO-NCHS. (Gibson, 2005). Data Riskesdas 2007 and2010 for the North Sulawesi shows the prevalence of underweight in children of school ageboys and girls is 17%. In the mean at the North Sulawesi province, the energy consumptionis lower than the national average (1381 vs. 1789 kilo calories). This study aims todetermine the effect of supplementation nuget fish eggs and protein adequacy, nutritionalstatus and cognitive function improvement in students with malnutrition status in SDNMalalayang. The study was quasi-experimental research design of the study and use onegroup pretest-posttest design. {Observation 1 (O1) → Tx → Observation 2 (O2)}. Theexperiment was conducted at the State Primary School Malalayang Malalayang ManadoCity District, in May to July 2011. The population in this study is a public elementary schoolchildren aged 7-12 years Malalayang the minimum sample size of the samples obtained bythe formula for the proportion of the population of data is limited (Lemeshow et al., 1997) at55. The results showed there were differences in mean nutritional status (BMI / U) of -0.57before and after supplementation with fish nuggets for a month p <0.01 in other words if thestudy was conducted at 99% confidence level the difference in nutritional status before andafter intervention ranged between -0.93 s / d -0.21 z score.Terdapat mean difference of -7.20 cognitive value before and after supplementation of fish nuggets for a month p <0.05in other words if the study was conducted at 95% confidence level the difference in valuecognitive impairment before and after the intervention ranged from -14.09 s / d -0.30 points.Conclusion. Giving Wonder Fish Supplementation positive influence in contributing to thefulfillment of the adequacy of protein by increasing protein intake after the intervention,nutrition and cognitive enhancement atatus students before and after the intervention.Suggestions need to diversify the development of street food recipes using local food andcontains values appropriate nutritional needs of students.